2021
DOI: 10.31729/jnma.6322
|View full text |Cite
|
Sign up to set email alerts
|

Febrile Seizure in Children Attending a Tertiary Care Centre in Western Nepal: A Descriptive Cross-sectional Study

Abstract: Introduction: Understanding a child with any episode of febrile seizure is important so that special attention could be given. The objective of this study was to find the prevalence of febrile seizure in children attending a tertiary centre in western Nepal. Methods: A descriptive cross-sectional study was performed in a tertiary care centre at the department of Pediatrics after taking approval from the Institutional Review Committee. Study was conducted among the children presented with febrile seizure from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
1
2
0
1
Order By: Relevance
“…8 A study conducted in a tertiary care centre in Western Nepal reported the prevalence of febrile seizure in children to be 4.61% which was lower when compared to our study. 7 A study conducted in India found hyponatremia in 37.5% of the total febrile seizure cases similar to our study. 9 A study conducted in Karnataka among cases of febrile seizure found similar results.…”
Section: Discussionsupporting
confidence: 90%
“…8 A study conducted in a tertiary care centre in Western Nepal reported the prevalence of febrile seizure in children to be 4.61% which was lower when compared to our study. 7 A study conducted in India found hyponatremia in 37.5% of the total febrile seizure cases similar to our study. 9 A study conducted in Karnataka among cases of febrile seizure found similar results.…”
Section: Discussionsupporting
confidence: 90%
“…La convulsión febril simple se presentó como diagnóstico retrasado, asociado a infección viral similar a lo reportado en otro estudio y no parece en esta situación que la consulta previa haya influido en (17) la evolución . Sin embargo, la potencial omisión de una infección del SNC en un paciente que consulta por fiebre y vómitos obliga a extremar el alerta en la consulta inicial.…”
Section: Discussionunclassified
“…These seizures are usually benign and self-limiting but may be associated with an increased risk for the development of epilepsy in later life, especially if the seizures are complex (Jongruk et al, 2022). While the exact pathophysiology of febrile seizures is unclear, a number of factors and features are reported to be associated with their occurrences, such as a family history of febrile seizures, recent vaccinations, and the deficiency of certain minerals (Duffy et al, 2017;Shrestha et al, 2021). Iron is an essential nutrient required for synthesizing hemoglobin and normal brain development and function (McCann et al, 2020).…”
Section: Introductionmentioning
confidence: 99%